Market Needs and Regulatory Impact on the Development of Islamic Economic Law: Strategic Quality Improvement Measures - Freddy Hidayat; Martoyo Martoyo; Afrik Yunari; Syifa'ul Hisan (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
The development of Islamic economic law education is strongly influenced by market dynamics and regulatory frameworks, positioning law as an essential engineering tool for economic development. This paper examines how these factors shape the Islamic Economic Law program at UIN Kiai Haji Achmad Siddiq Jember, focusing on its role in producing legal experts capable of designing and supporting sharia-compliant economic systems. By integrating the socio-legal perspective, the study highlights how law operates not only as a normative framework but also as an instrument to engineer financial stability, facilitate Islamic market transactions, and foster innovation in sharia-based industries. Using international best practices in curriculum design, governance, and graduate competency development, the paper proposes strategic measures to elevate program quality toward superior accreditation standards. Recommendations include curriculum reform aligned with evolving financial technologies, faculty capacity-building, and industry collaboration, ensuring graduates are equipped to meet national and global demands in Islamic economic jurisprudence.